Penerapan Relaksasi Slow Deep Breathing dan Relaksasi Benson Untuk Menurunkan Intensitas Nyeri Post SC - Noviyanti, Yunita; Yanita Trisetiyaningsih (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Caesarean section delivery can have a negative impact on the mother both physically and psychologically, where the psychological impact is that the mother experiences fear and anxiety about the pain that arises after the analgesic wears off. Based on data from December 2022, it was found that the pain felt by post-cesarean section mothers was 80% out of 100% experiencing pain on a scale of 6-7. Non-pharmacological pain management post-cesarean section that can be used is one of them, slow deep breathing relaxation and Benson relaxation. Purpose: The aim of this research is implementing slow deep breathing therapy and relaxation therapy to reduce pain intensity in mothers post-SC. Method: The research method uses a case study approach, with data collection techniques through interviews, observation, physical examination and documentation of the implementation of slow deep breathing relaxation and Benson relaxation. Conclusion: Slow deep breathing therapy and relaxation therapy are effective in reducing pain intensity in post-CS mothers.